Calculating the market value of riskless cash flows - Ruback, Richard S. (Journal of Financial Economics, 1986)
This paper uses arbitrage arguments to calculate the market value of riskless after-tax cash flows. The market value equals the present value of riskless after-tax cash flows discounted at the after-corporate-tax riskless interest rate. The market value equals the adjusted present value of riskless after-tax cash flows only when the incremental debt used in the adjusted present value calculations equals the market value of the remaining after-tax cash flows. Also, the analysis provides valuation formulas when interest and tax rates are certain but not uniform and when interest rates are uncertain.